GNE Myopathy With Novel Mutations and Pronounced Paraspinal Muscle Atrophy - Soule, Tyler; Phan, Cecile; White, Chris; Resch, Lothar; Lacson, Atilano; Martens, Kristina; Pfeffer, Gerald (Frontiers in Neurology, 2018)
GNE myopathy is characterized by distal muscle weakness, and caused by recessive mutations in GNE. Its onset is characteristically in young adulthood, although a broad spectrum of onset age is known to exist. A large number of mutations in GNE are pathogenic and this clinical phenotype can be difficult to differentiate clinically from other late-onset myopathies. We describe two families with novel mutations in GNE, and describe their clinical and MRI features. We also describe the presence of striking paraspinal muscle involvement on MRI of the lumbar spine, which is an under-recognized feature of GNE myopathy.